Determination of nicotine in newborn meconium by high-Resolution ambient mass spectrometry using wooden-Tip spray - Wang, Xinrong; Yang, Mingyu; Xiao, Hui; Liu, Danping; Pan, Lu; Zhang, Liuyang; Yang, Yan; Lu, Qing; Liu, Yanqiu; Yang, Xiao; Yang, Bicheng (Frontiers in Chemistry, 2023)
Prenatal exposure to nicotine that are mainly produced from tobacco smoke has been reported to affect infants. Therefore, nicotine exposure is one of important health concerns for newborn screening. Detecting nicotine and its metabolites such as cotinine in meconium were widely used to evaluate the tobacco exposure of pregnancy. In this study, disposable wooden tips were applied for touch sampling of meconium from newborn infants, and then were directly mounted on mass spectrometer (MS) to perform rapid screening of nicotine and cotinine. Choice of extraction/spray solvents was optimized. The limits of detection, reproducibility, linear response for direct analysis of meconium were also investigated. It is found the limits of detection (S/N = 3) to be as low as 0.36 ng/mg and 1.18 ng/mg for nicotine and cotinine, respectively, while the limits of quantitation (S/N = 10) to be 1.19 ng/mg and 3.94 ng/mg for nicotine and cotinine, respectively. The relative standard deviations (RSD) were found to be at 8.4 – 19.8 % (n = 6) for nicotine and cotinine, a good linear range from 5 – 500 ng/mL (R2 > 0.99). These analytical performances are well-accepted levels for ambient MS analysis. In this study, evaluation of nicotine and cotinine in 22 puerpera volunteers were conducted by the established wooden-tip spray mass spectrometry (WTS-MS). These results showed that WTS-MS would be useful for newborn screening of nicotine and cotinine in meconium with high reproducibility, speed, sensitivity, and specificity. Owing to the use of disposable wooden tips that involves no sample preparation and no chromatographic separation, our results show that WTS-MS is a powerful tool for determination of nicotine in newborn meconium.